THE RELIGIOUS CONVERSION PROCESS OF THE MALAYSIAN CHINESE MUSLIM CONVERTS - Loo Tuck Yee; Nadiyah Elias; Mariny Abdul Ghani (Journal of Islamic, Social, Economics and Development, 2019)
This study explores the religious conversion process in the context of the Malaysia Chinese Muslim convert and Islamic perspective. It is a qualitative study. Five participants were taking part. Data were collected by semi-structured interviews and analysed by using ATLAS.ti.8.2 software. Five stages of conversion process were identified in this study: (a) initial attraction, (b) absorption (c) adaptation, (d) assimilation and (d) integration. Instead of religious maturity, this study identified the process based on intrapsychic and interpersonal growth.